Discovery of two new Cortinarius species in Southern China - Dang, Yuxiao; Zhu, Mengjia; Keyhani, Nemat O.; Wu, Ziyi; Qiu, Chenghao; Xiong, Jinming; Pu, Huili; Lin, Longbing; Xiong, Chengjie; Zhao, Zhiying; Zheng, Minghai; Mu, Taichang; et al. (Frontiers in Microbiology, 2025)
IntroductionCortinarius are globally distributed mushrooms, all of whom form mycorrhizae, and are characterized by rust-brown to brownish-red spores. The high species richness of the genus results in significant morphological diversity overall, alongside high similarity among closely related species, leading many taxonomists to concentrate their studies on specific infrageneric groups.MethodsSpecimens were noted and collected from Fujian Province, China. Genomic DNA was extracted from specimens and the nucleotide sequences of two loci (ITS AND nr LSU) were determined and used to construct phylogenetic trees. Microscopic features were observed using an optical microscope. Fluorescence reactions were examined using a fluorescence microscope.ResultsWe describe two new species of Cortinarius, C. griseoaurantinus (subgenus Leprocybe) and C. yonganensis (subgenus Dermocybe), from Fujian Province, Southern China. Comprehensive morphological descriptions, color photographs of fresh basidiomata, photographs of microscopic characters, and phylogenetic trees are provided.DiscussionThese data identify new species of Cortinarius, enhancing the understanding of the genus and the ecological relationships. The developed keys provide a reference for the further analysis of the evolution and geographic distribution of these fungi.